The Contribution of Agroforestry To Rural Household Income at the Grand Forest Park - Riani, Windy Mardiqa; Sunkar, Arzyana; Sundawati, Leti (Journal of Rural Indonesia [JORI], 2015)
Agroforestry is a form of land management system that combines agriculture with trees. Agroforestry have been much practiced in rural areas to enhance the area’s economic conditions. It is often practiced on com- munity-owned land through the harvesting of fruits, timbers, and food plants like paddy, tubers, spices, and vegetable. As indicated  by various literatures, most of the contributions were attained from fruits, followed by food plant and timbers. Such would raised a question as to the economic contribution of agroforestry if practiced on government-owned land that do not allow the cutting of timbers and intensive agriculture such as in protected areas that have specific function as biodiversity preservation sites. This research was carried out in Wan Abdul Rachman Grand Forest Park, a protected area within the Province of Lampung, Indonesia. The sampled areas comprised of three villages directly adjacent to the Park where the majority of the people worked in agroforestry farms within the Park. Respondents were selected through random sampling method. The role of agroforestry in incresing farm income were evident by its contribution which amounted to 45.96% of the total household’s income through the selling of fruits and food plants to the local wholesalers. Income from agroforestry were able to meet almost half (49,26%) of the rural livelihood’s needs. The most dominant plants that generated high incomes in the three villages were coffee (Anacolosa frutescens) and cocoa (Theobroma cacao).Keywords: agroforestry, wan abdul rachman, grand forest park, rural household